2016
DOI: 10.1136/bmjopen-2015-007919
|View full text |Cite
|
Sign up to set email alerts
|

Depressive symptoms, life satisfaction and prevalence of sleep disturbances in the general population of Germany: results from the Heinz Nixdorf Recall study

Abstract: ObjectivesIt appears that not only depression, but also low life satisfaction (LS), is related to sleep disorder in the general population. We evaluate whether the prevalence of sleep disorder attributable to depressed mood is greater among participants with low LS.Setting, participants and outcome measuresAnalysis of cross-sectional data from 3880 cohort members from the German Heinz Nixdorf Recall study (2006–2008) aged 51–81 years. Standard mood (Center for Epidemiological Studies Depression scale (CES-D) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 49 publications
2
40
1
7
Order By: Relevance
“…Furthermore, we found that patients without depressed mood had lower severity of depression (especially of core symptoms), insomnia, anxiety, and suicidal ideation and a higher level of social functioning than those with depressed mood. Partly consistent with our findings, a strong association between depressed mood and sleep disturbance was seen in the general population of Germany [3]. Hence, our findings lead us to speculate that absence of depressed mood in MDD is associated with a lower illness burden.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Furthermore, we found that patients without depressed mood had lower severity of depression (especially of core symptoms), insomnia, anxiety, and suicidal ideation and a higher level of social functioning than those with depressed mood. Partly consistent with our findings, a strong association between depressed mood and sleep disturbance was seen in the general population of Germany [3]. Hence, our findings lead us to speculate that absence of depressed mood in MDD is associated with a lower illness burden.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, a strong association has been reported between depressed mood and MDD, and evidence has been presented that low socioeconomic status and social isolation contribute to depressed mood [2]. Also, an association between depressed mood and sleep disturbance has been reported based on a cohort of 3880 patients in Germany [3]. Moreover, depressed mood has been proposed as an independent risk factor for 22-month mortality in physically ill patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, such an increase in total sleep time is not necessarily suggestive of better or more efficient sleep. Indeed, depressive symptoms such as fatigue, anhedonia, and physical inactivity may lead to more time spent sleeping throughout the night and day (61), but less time obtaining efficient, restful, and uninterrupted sleep (18). …”
Section: Discussionmentioning
confidence: 99%
“…In a non-clinical sample, depressive symptoms were shown to be strongly linked to poor sleep quality (18). In clinical samples, difficulty initiating and/or maintaining sleep has been reported in about three-quarters of depressed patients (1921).…”
Section: Introductionmentioning
confidence: 99%
“…For sample calculation, it was considered the population of 67 thousand inhabitants in the municipality of the investigation within the chosen age range, according to the inclusion criteria, the anticipated prevalence of poor sleep quality of 38%, (13) the statistical power of 80% (β=20%), the significance level of 5% (α=0.05) and the design effect of 3.0, 10% increase for possible losses and totaling a probabilistic sample of 777 individuals. Patients aged ≥18 years of age, of both genders, living in the municipality, local public health system users, and without previous medical diagnosis of sleep disorder were included.…”
Section: Methodsmentioning
confidence: 99%